Passage to promise land : voices of Chinese immigrant women to Canada - Poy, Vivienne, 1941- (McGill-Queen's University Press, 2013)
This book is the study of Chinese immigration to Canada from the end of the Second World War to the present day. Traces the evolution of immigration policy through the stories of Chinese immigrant women. It also shows how the Chinese community developed alongside changes in immigration regulations, and why the immigration of Chinese families to Canada became commonplace in the 1970s. It includes the very first mention of Chinese women's immigration in Canada's Parliament in 1879, to the end of the twentieth century.